2013
DOI: 10.3892/mmr.2013.1878
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of orientin on hydrogen peroxide-induced apoptosis in SH-SY5Y cells

Abstract: Neurodegenerative diseases remain a global issue which affects the ageing population. Efforts towards determining their aetiologies to understand their pathogenic mechanisms are underway in order to identify a pathway through which therapeutic measures can be applied. One such pathogenic mechanism, oxidative stress (OS), is widely considered to be involved in neurodegenerative disease. Antioxidants, most notably flavonoids, have promising potential for therapeutic use as shown in in vitro and in vivo studies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 38 publications
3
38
0
Order By: Relevance
“…In astrocytes, the concomitant incubation with MnL4 reduces it, whereas in SH-SY5Y, MnL4 is ineffective. An anti-apoptotic effect of antioxidants has been described in SH-SY5Y treated with noxious stimuli like MPP þ [36], 1,2-diacetylbenzene [37] or hydrogen peroxide [38]. In those reports, an exogenous oxidant stimulus has been employed; on the contrary, as already described [20], oxaliplatin is not a direct oxidant molecule.…”
Section: Discussionmentioning
confidence: 99%
“…In astrocytes, the concomitant incubation with MnL4 reduces it, whereas in SH-SY5Y, MnL4 is ineffective. An anti-apoptotic effect of antioxidants has been described in SH-SY5Y treated with noxious stimuli like MPP þ [36], 1,2-diacetylbenzene [37] or hydrogen peroxide [38]. In those reports, an exogenous oxidant stimulus has been employed; on the contrary, as already described [20], oxaliplatin is not a direct oxidant molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Yu et al [45] showed that orientin impeded the Aβ 1-42 -induced cellular apoptosis, and improved cognitive impairments and mitochondrial deficiency in AD rats. In addition, orientin had other physiological effects, such as antioxidant, antiglycation [46], and protective effect from mitochondrial oxidative stress-induced apoptosis [47]. Isoorientin, as an isoform of orientin, alleviates LPS-induced pro-inflammatory mediators by inhibiting the activation of mitogen-activated protein kinases (MAPKs) and nuclear factor κB (NF-κB) [48].…”
Section: Impairment Of Fasting Glucose and Glucose Tolerance Is Relatmentioning
confidence: 99%
“…Several recent studies have demonstrated that orientin exerts a variety of pharmacological effects, including antioxidant, anti-inflammatory, and neuroprotective effects [24,25]. For example, orientin (20 mg/kg and 40 mg/kg, intragastric administration) has shown significant antioxidant properties in improving the neuronal ultrastructure in the hippocampus of D-galactose-aged mice [26].…”
Section: Introductionmentioning
confidence: 99%